Tracking movements and growth of post-hatchling to adult hawksbill sea turtles using skeleto+iso - Turner Tomaszewicz, Calandra N.; Liles, Michael J.; Avens, Larisa; Seminoff, Jeffrey A. (Frontiers in Ecology and Evolution, 2022)
In the eastern Pacific Ocean, hawksbill sea turtles (Eretmochelys imbricata) are adapted to use coastal habitats and ecosystems uncharacteristic of most other sea turtles. Once considered extirpated from this region, hawksbills had sought refuge in estuaries, nesting on muddy banks among the tangles of mangrove roots. This population is at high risk of bycatch during fishing efforts in the estuaries (blast fishing) and adjacent coastal rocky reefs (gillnets), and is further impacted by habitat degradation from coastal development and climate change. The conservation and population recovery of hawksbills in this region is highly dependent on management actions (e.g., nest relocation, habitat protection, bycatch mitigation), and a better understanding of how hawksbills use and move between distinct habitats will help prioritize conservation efforts. To identify multi-year habitat use and movement patterns, we used stable carbon (δ13C) and nitrogen (δ15N) isotope analysis of skin and bone growth layers to recreate movements between two isotopically distinct habitats, a nearshore rocky reef and a mangrove estuary, the latter distinguishable by low δ13C and δ15N values characteristic of a mangrove-based foodweb. We applied skeletochronology with sequential δ13C and δ15N analysis of annual growth layers, “skeleto+iso”, to a dataset of 70 hawksbill humeri collected from coastal El Salvador. The results revealed at least two unique habitat-use patterns. All turtles, regardless of stranding location, spent time outside of the mangrove estuaries during their early juvenile years (<35 cm curved carapace length, CCL, age 0–5), showing that an oceanic juvenile stage is likely for this population. Juveniles ca. >35 cm then began to recruit to nearshore areas, but showed divergent habitat-use as some of turtles occupied the coastal rocky reefs, while others settled into the mangrove estuaries. For turtles recruiting to the estuaries, settlement age and size ranged from 3–13 years and 35–65 cm CCL. For the adult turtles, age-at-sexual-maturity ranged from 16–26 years, and the maximum reproductive longevity observed was 33 years. The skeleto+iso also showed that adult hawksbills have long-term habitat fidelity, and the results demonstrate the importance of both mangrove estuary and nearshore rocky reefs to the conservation of hawksbills in the eastern Pacific.